The Effectiveness of Clinical Pharmacist-Led Consultation in the Treatment of Infectious Diseases: A Prospective, Multicenter, Cohort Study - Zhang, Jiaxing; Li, Xiaosi; He, Rui; Zheng, Wenyi; Kwong, Joey Sum-wing; Lu, Ling; Lv, Tianyi; Huang, Rong; He, Mei; Li, Xiaoyan; Wang, Xue; Fang, Qin; et al. (Frontiers in Pharmacology, 2020)
Background Antimicrobial resistance (AMR) is a serious global health threat and leads to a huge challenge to infectious diseases (ID) treatment. To tackle AMR, regional ‘Antimicrobial Stewardship Programs’ (ASP) have been implemented in many countries. Due to insufficient clinical pharmacy resources, a major intervention mode of ASP in China is through clinical pharmacist-led consultation (CPC). The current study aims to prospectively evaluate this intervention and compare the effectiveness of CPC served by ID and non-ID clinical pharmacists. Methods We conducted a prospective and multicenter cohort study based on a regional registry database in 17 hospitals in Western China, including consecutive patients with ID between April 2017 and December 2019. Baseline characteristics including sex, age, liver and kidney function, comorbidity, infection severity were prospectively collected and recorded. The main exposure of interest was whether the attending physician adopted recommendations of the clinical pharmacist in the therapeutic scheme. The outcome was the infection effective response, assessed during day 3–7 after completing CPC. Multivariate analyses were performed by generalized linear mixed models. Results A total of 2,663 ID patients were included in the final analysis according to the predesigned inclusion and exclusion criteria. The number of patients whose treatment followed and did not follow the pharmacists’ suggestion was 2,529 and 134, respectively. CPC intervention could improve the ID patient prognosis in the context of other confounders controlled (Adjusted Odds ratio(AOR)=1.838, 95%Confidence Interval(CI)=[1.212, 2.786]), and the effectiveness of CPC served by ID and non-ID clinical pharmacists might be equivalent (AOR=0.958, 95%CI[0.740, 1.240]). Special consultation (AOR=1.832, 95%CI[1.106, 3.035]) and surgical treatment of infectious sites (AOR=1.380, 95%CI[1.039, 1.834]) had positive influences on the patient prognosis, while hypoalbuminemia (AOR=0.694, 95%CI[0.523, 0.921]), liver dysfunction (AOR=0.705, 95%CI[0.559, 0.889]), presence of high-risk factors (AOR=0.775, 95%CI[0.613, 0.980]), and increased infection severity (AOR=0.631, 95%CI[0.529, 0.753])were associated with a decrease in effective response rate, independently. Conclusion This study suggests that CPC is a promising pharmacist-led intervention to improve ID treatment, and it can achieve standardization among clinical pharmacists with different backgrounds by some measures. Policy/decision-makers should promote this intervention mode in developing countries or regions where there is an insufficient number of clinical pharmacists.